2021
DOI: 10.3390/ijms222413614
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Pathogenicity and Virulence of Staphylococcus pettenkoferi: An Emerging Pathogen

Abstract: Staphylococcus pettenkoferi is a coagulase-negative Staphylococcus identified in 2002 that has been implicated in human diseases as an opportunistic pathogenic bacterium. Its multiresistant character is becoming a major health problem, yet the pathogenicity of S. pettenkoferi is poorly characterized. In this study, the pathogenicity of a S. pettenkoferi clinical isolate from diabetic foot osteomyelitis was compared with a Staphylococcus aureus strain in various in vitro and in vivo experiments. Growth kinetics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 62 publications
4
14
0
Order By: Relevance
“…Biofilm-encoding genes (i.e., icaABCD and rsbUVW) and regulator-encoding genes (i.e., agr, mgrA, sarA, and seaS), also occurring in S. aureus , were identified by the whole-genome analysis of S. pettenkoferi strain. These features confirm a clinical relevance of this bacterium [ 16 ].…”
Section: What Do We Actually Know About Staphylococcus Pett...supporting
confidence: 75%
See 2 more Smart Citations
“…Biofilm-encoding genes (i.e., icaABCD and rsbUVW) and regulator-encoding genes (i.e., agr, mgrA, sarA, and seaS), also occurring in S. aureus , were identified by the whole-genome analysis of S. pettenkoferi strain. These features confirm a clinical relevance of this bacterium [ 16 ].…”
Section: What Do We Actually Know About Staphylococcus Pett...supporting
confidence: 75%
“…S. pettenkoferi is CoNS, first described in 2002 [ 3 , 10 ]. Since then, there have been several reports describing the involvement of S. pettenkoferi in blood infections and osteomyelitis, mainly in immunocompromised patients or patients with comorbidities, among which diabetes mellitus appears to be the most frequently observed [ 3 , 4 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. S. pettenkoferi was also isolated from other sources, such as wounds and ulcers, vaginal abscesses, and frontal sinus—in all cases, with other organisms isolated in culture [ 17 ].…”
Section: What Do We Actually Know About Staphylococcus Pett...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ruminococcus , the abundance of which decreased in Uox -knockout mice, is also known as a SCFAs-producer [ 22 ]. Staphylococcus is known as a pathogenic microorganism that increases the risk of pathogenic invasion and intestinal inflammation [ 58 ]. In the current study, Staphylococcus showed a significant positive correlation with the kidney injury markers and renal fibrosis biomarkers, indicating that it might play a role in HN progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, S. pettenkoferi is notably a frequent bacterium isolated from DFOM, suggesting that it could also be involved in the pathophysiology of these infections [ 26 ]. Recently, our team described the virulence of one clinical strain isolated from this condition and, notably, its ability to proliferate in phagocytes and to persist inside macrophages and its virulence was confirmed in the zebrafish model of infection [ 27 ].…”
Section: Introductionmentioning
confidence: 99%